(untitled) (The Review of Diabetic Studies, 2025)
Health informatics and cybersecurity have become essential pillars in modern healthcare transformation, particularly as digital ecosystems expand and clinical operations rely heavily on electronic data. This integrative review examines how robust informatics infrastructures and security frameworks collectively enhance digital safety, strengthen data integrity, and improve clinical performance. Evidence from longitudinal studies indicates that secure electronic health systems, decision-support tools, and interoperable platforms significantly reduce documentation errors, support accurate clinical decision-making, and enhance workflow efficiency. Simultaneously, cybersecurity mechanisms—such as encryption, identity access management, and real-time threat monitoring—mitigate risks of data breaches and operational disruptions. The findings highlight that the synergy between informatics and security readiness is critical for maintaining trust, optimizing patient safety, and enabling resilient healthcare delivery. The review concludes by identifying future priorities for strengthening governance, workforce capabilities, and technological integration.